Latent and Asymptomatic Toxocara Infection among Young Population in Northwest Iran: The Necessity of Informing People as a Potential Health Risk - Tina Momeni; Mahmoud Mahami-Oskouei; Esmaeil Fallah; Abdolrasoul Safaiyan; Leyla Mahami-Oskouei (Scientifica)
Objectives. This study was designed to determine the frequency of anti-Toxocara antibodies in youngsters aging from 2 to 20 years in northwest Iran. Materials and Methods. 397 samples were taken randomly almost equally from four locations in Urmia, west Azerbaijan, during August 2014 to September 2015. Anti-Toxocara IgG antibody assays were done on sera by using ELISA kit (IBL, Germany). In order to prevent cross-reaction, the samples of the patients who are infected with other parasites in stool exam, especially Ascarididae family, were also excluded. SPSS 16.0 software was used for statistical analysis. Results. 12 (3%) of the serum samples were positive for anti-Toxocara IgG. According to the Chi-square analysis, risk factors such as mother’s educational level, keeping dogs or cats as pets, and history of coughing were related to Toxocara infection (P<0.05). There was no relationship between toxocariasis and gender, history of onychophagy, pica, fever, abdominal pain, and anorexia; however, we found a significant relationship between Toxocara infection and chronic coughing (P=0.045). Conclusion. Toxocariasis in northwest Iran can be considered as a public health problem. This study may also help to increase the awareness about this infection.